Recommendations to Improve Accessibility of Sexuality Education for Individuals with Intellectual or Developmental Disabilities: A Qualitative Study. Issue 1 (2nd January 2021) - Schmidt, Elizabeth K.; Robek, Natalie; Dougherty, Megan; Hand, Brittany N.; Havercamp, Susan; Sommerich, Carolyn; Weaver, Lindy; Darragh, Amy
Abstract: Introduction: According to the World Health Organization, sexuality education (SE) is considered a human right and aims to increase understanding, decrease abuse, unplanned pregnancies, and sexually transmitted infections. Yet, individuals with intellectual or developmental disabilities are less likely to receive or SE is primarily focused on safety and abuse prevention, despite best practice being comprehensive, inclusive, and positive approaches to SE. Methods: We performed a sub-analysis from a larger study to identify recommendations to improve accessibility of SE using interviews and focus groups with individuals with intellectual or developmental disabilities, parents, healthcare providers, and educators. Results: All participants recommended using educational guides, direct, explicit instruction, videos, visuals, and universal design for learning (UDL). Participants also recommended a variety of settings, including one-on-one, group, a combination, or technology. Conclusions: Educational guides, visuals, videos, UDL, and direct, explicit instruction should be utilized when providing SE to individuals with intellectual or developmental disabilities. Settings and modalities should be determined dependent on the individuals' preferences, abilities, and fit. Further, worksheets and handouts may be useful in educational and healthcare settings, while role playing and modeling may be useful in educational, community-based and/or home settings, and parents require additional education and training to support their children.